The governance of policy reforms in southern Europe and Ireland : social dialogue actors and institutions in times of crisis - Papdakis, Konstantinos; Ghellab, Youcef (International Labour Office, 2014)
This edited volume provides an overview of the changes that have occurred in industrial relations systems in Southern Europe and Ireland as a result of the debt crisis and subsequent fiscal consolidation policies. The authors take stock of developments and consider policy implications.